Childbearing Probabilities During the First Years of Marriage Among Egyptian Women (Damascus University Journal for the economic and Political sciences, 2024)
Prolonging the period between marriage and the first birth reduces the effective age of childbearing in a woman and thus fewer children during her life. This paper studied the interval between marriage and the first birth in each of the years 2005 and 2014, to see if a change has occurred or not in the length of this interval, the probability of childbearing in it, and the effective factors. The life table and Cox Proportional hazard model were used and the 2005 and 2014 Egypt Demographic and Health Survey. The differences between 2005 and 2014 appeared very slight in the period that 50% of women take to get their first birth after 3 years of marriage, and also concerning the probability of a woman having her first birth during the first three years of marriage. There was no difference between the two years in terms of the variables with a significant effect on that interval, as all the variables included in the analysis showed a very strong effect, except access to mass or social media at least once a week. Place of residence, women currently working and knowledge of ovulatory cycle has a statistically significant negative influence on the interval between marriage and the first birth. While the level of education of both partners, usage of contraceptives, and age at first marriage had a statistically significant positive influence on that period. This study shows that it is necessary to raise awareness of the danger of female marriage under the appropriate age, the need for the couple to be reassured about the continuation of the marriage before deciding to have a child and push poor families to enroll their children in the different stages of education by giving them some financial aid, which compensates them for sending their children to work.
Keywords: Childbearing; Egyptian women; First birth interval